Optimization Of Drilling Strategies To Increase Production Efficiency In The Field Of Production Geology - Citra Wahyuningrum; Lady Antira; Edo Stanzah (Pusat riset dan Inovasi Nasional, 2024)
This research aims to investigate and optimize drilling strategies as an effort to increase production efficiency in the geological context of oil and gas production. Effective drilling is a key element in the exploitation of hydrocarbon resources, and this research combines geological analysis and drilling techniques to achieve optimal results. This study begins with an in-depth characterization of the physical and chemical properties of the reservoir rocks to understand the geological challenges faced. Next, existing drilling techniques are evaluated and analyzed in the context of a particular production field. The results of this analysis are the basis for developing an integrative model that combines aspects of geology and drilling techniques.Through this approach, this research aims to identify potential improvements in drilling strategies that could significantly increase production. Simulation and modeling results illustrate the positive impact of implementing optimized drilling strategies on production efficiency and hydrocarbon recovery. The conclusions of this research provide a new perspective on the importance of integration between geological science and drilling techniques in achieving efficient production goals. It is hoped that these findings will provide practical guidance for the production geology industry to increase the sustainability of oil and gas production.